Distinct peptide loading pathways for MHC class II molecules associated with alternative Ii chain isoforms. - Bikoff, E; Kenty, G; Van Kaer, L (1998)
Mutant mouse strains expressing either p31 or p41 Ii chain appear equally competent with respect to their class II functional activities including Ag presentation and CD4+ T cell development. To further explore possibly divergent roles provided by alternative Ii chain isoforms, we compare class II structure and function in double mutants also carrying a null allele at the H2-DM locus. As for DM mutants expressing wild-type Ii chain, Aalpha(b)Abeta(b) dimers present in DM-deficient mice expressing either Ii chain isoform appear equally occupied by class II-associated Ii chain-derived peptides (CLIP). Surprisingly, in functional assays, these novel mouse strains exhibit strikingly different phenotypes. Thus, DM-deficient mice expressing wild-type Ii chain or p31 alone are both severely compromised in their abilities to present peptides. In contrast, double mutants expressing the p41 isoform display markedly enhanced peptide-loading capabilities, approaching those observed for wild-type mice. The present data strengthen evidence for divergent class II presentation pathways and demonstrate for the first time that functionally distinct roles are mediated by alternatively spliced forms of the MHC class II-associated Ii chain in a physiologic setting.